Kajian Sistematik: Efek Gen Multi Drug Resistance-1 pada Farmakokinetik Klopidogrel - Niruri, Rasmaya; Noviyani, Rini; Rahajeng, indah Mei (Jurnal Kefarmasian Indonesia, 2019)
Multi Drug Resistance-1 (MDR-1) gene polymorphisms encoding for P-glycoprotein can affect clopidogrel intestinal absorption. This systematic review aim to identify the impact of MDR-1 gene 3435 variants on clopidogrel pharmacokinetics. Literature review were retrieved from MEDLINE, Science Direct, Scopus, Clinical Key, ProQuest and Google Scholar databases. The articles are critically reviewed and analyzed to answer this systematic review’s aim. The result showed that, in patients with cardiovascular disease, the peak plasma concentration (Cmax) and the total area under the plasma concentration–time curve (AUC) of clopidogrel and its active metabolites were lower in 3435TT compared to 3435CC. Nevertheless, the variants of MDR-1 gene were not significantly correlated to the plasma concentration in healthy subjects. Clopidogrel pharmacokinetic profile varied widely between MDR-1 3435 variants and subjects.